Evaluación de dos etapas de aplicación de ozono con tres dosis, en el comportamiento poscosecha de Fresa (fragaria vesca), cosechado a diferentes índices de color, Cotopaxi, 2021-2022. - Guanoluisa Cofre, Ana Viviana (2022)
This research was carried out in Cotopaxi province, Eloy Alfaro parish, Salache campus at the laboratory of the Agronomic Engineering major. It aimed to evaluate the stages of ozone application with three doses in the post-harvest behavior of strawberry (Fragaria vesca), harvested at different color indices, Cotopaxi, 2021-2022. A randomized complete block design with a 2 x 2 x 3 factorial arrangement was applied, giving a total of 12 treatments and 36 experimental units. The applied ozone doses were 0, 0.3, and 0.6 ppm applied in pre-harvest and post-harvest. The indicators evaluated were incidence of physiopathies, weight loss, firmness, pH, total solids, ashes, and humidity. The following results were obtained: the best stage of the application was in pre-harvest because they presented better averages in each of the characteristics evaluated, reaching the fifth day of data collection with averages of 93.11% of physiopathies; 2.96% weight, 0.79 kg of firmness, 38% ash and 90.59% humidity, on the other hand, post-harvest presented 7.02 °Brix and 5.56 pH. The applied doses yielded positive results for 0.6 ppm, registering 91.67% of physiopathies; 2.83% weight loss; 7.34 ° Brix and 32.37% ash; and 5.94 pH concerning moisture; the doses did not show significant values. The best index for harvest was C1 (75% red) with averages of 93.33% physiopathies; 0.86 kg of firmness, and 90.41% moisture, while index C2 (90% red) presented 7.14 °Brix, 1.87% weight, and 6.08 pH in regards to ashes none of the indices showed significance.